BLADDER CANCER: INCIDENCE, ASSOCIATION, BASIS, GEOGRAPHY AND RISK FACTORS - Hayder Saadoon Qasim Alhilfi (European Scientific Journal, ESJ, 2015)
Objectives: The purpose of the study are to formulate an idea about the number of patients with bladder cancer in Missan city and those of them that are on treatment by the oncology center of the province. Also to point towards the most prevalent histo-pathologic finding and to put our hands on the probable effect of some risk factors on the incidence which indicate to the noticed association between the endemicity of schistosomiasis in the rural areas of Missan with bladder cancer. Methods: A descriptive study was conducted in Al-Shafaa oncology center. The total numbers of patients involved in the study were 55, through period from July 2014 to April 2015. Results: Men were most affected 78.18% (43) than women 21.82% (12).Most of patients were smokers 80% (44). The mean age affected was between 60-70 years 34.55% (19). The urban peoples were most present 65.45% (36). Among most histopathology, the transitional cell carcinoma was the most type 87.27% (48), which mostly invasive 63.64% (35), while the most grading was grade III 47.28% (26) and the most staging was T2 45.45% (25). Conclusion: The incidence of squamous cell carcinoma was, 12.73% of the subjects of the study, which is associated with schistosomiasis.